Peta Kajian: Analisa Bibliometrik pada Bidang Manajemen Pendidikan Islam - Khoirotul Ni'amah (Mukaddimah: Jurnal Studi Islam, 2025)
The study of Islamic education management in Indonesia has long been a subject of research and has become a significant topic in scholarly publications. To understand research on Islamic education management, this study explores several studies using bibliometric methods. The analysis in this article is limited to the period 2017-2025 and relies on data from the Scopus database. This study analyzed 114 articles from 390 authors to map the knowledge gap in Islamic education management research. Data analysis used VOSviewer and Biblioshiny to analyze metadata for each Scopus-indexed article in CSV (comma-separated values) format. This study identified several recommended keywords that could serve as the primary focus of future research in Islamic education management. Some of these keywords are strategic management, educational policy and politics, transformative education, educational evaluation, multicultural education management, and curriculum studies. Keywords: Bibliometric Analysis, Educational Management Research, Mapping Knowledge.